Evaluation of Antibiotic Use in Pediatric Patients with Bronchopneumonia Hospitalized at K.R.M.T Wongsonegoro Hospital - Nastiti, Nindita Sari; Hanum, Dayyana Rizkya; Oktavia, Shelomita Risti; Dewi, Rissa Maharani (Sciences of Pharmacy, 2026)
Bronchopneumonia is a respiratory tract infection affecting the bronchi and lungs and remains one of the leading causes of mortality among children worldwide. Antibiotics are the mainstay of therapy; however, their high utilization necessitates evaluation to ensure rational use. At K.R.M.T. Wongsonegoro Hospital, Semarang, bronchopneumonia was the leading infectious disease among pediatric patients in 2023, highlighting the need for a comprehensive assessment of antibiotic prescribing practices. This study aimed to determine the profile of antibiotic use and evaluate both qualitative and quantitative appropriateness of antibiotic therapy among pediatric inpatients with bronchopneumonia. A descriptive, retrospective, cross-sectional study was conducted involving 281 pediatric inpatients aged 0–18 years hospitalized with bronchopneumonia throughout 2023. Qualitative antibiotic appropriateness was evaluated using the Gyssens method, while quantitative utilization was analyzed via the Defined Daily Dose (DDD)/100 inpatient-days system. Ceftriaxone was the predominant therapy, both as monotherapy and in combination with azithromycin. Qualitative analysis revealed notable irrationalities, characterized primarily by incorrect dosing intervals and inappropriate dosages, alongside truncated treatment durations. Quantitatively, ceftriaxone exhibited the highest consumption rate, dominating the Drug Utilization 90% (DU90%) segment. These findings reveal suboptimal antibiotic utilization patterns, underscoring an urgent need for institutional prescription audits and targeted educational interventions to mitigate the risk of localized antimicrobial resistance.